Decomposition Analysis of Energy Carbon Emission Factors in Beijing-Tianjin-Hebei. Issue 4 (February 2020) - Fan, Zhiguo; Zhang, Shaolin
Abstract: With the rapid economic development of Beijing-Tianjin-Hebei region, the problem of environmental pollution cannot be ignored. Especially in recent years, the haze weather, the increase of carbon dioxide emissions, the development of Beijing, Tianjin and Hebei has brought a negative impact. Now, the primary energy consumption of the three regions of Beijing, Tianjin and Hebei is decomposed into five factors including population, economy, industrial structure, energy intensity and energy consumption structure by using LMDI decomposition method. The results show that: overall population and per capita GDP promote the growth of carbon emissions, and overall industrial structure effect, energy intensity effect and energy consumption structure factors inhibit the growth of carbon emissions. The energy intensity of the secondary industry and the tertiary industry has a very significant inhibiting effect on the growth of carbon emissions.